Clinical and microbiological profile of necrotizing fasciitis - Halbhavi, Subhash N.; Reddy, Ramachandra; Kalburgi, E. B.; Poulose, Arunima; Gowd, Y. C. Veerabhadra (International Surgery Journal, 2018)
Background: Necrotizing fasciitis, is a spectrum of diseases where necrosis of deeper soft tissue is by an infective microorganism. It is a life-threatening infectious disease with mortality rate ranging from 17% to 34%. Understanding patho-physiology plays an important role in providing better medical or surgical care. Aim of the present study was to find out the most common microorganisms causing Necrotizing Fasciitis, sensitivity pattern of the isolated organisms and effective antibiotic therapy. Methods: This is a prospective observational study done in HSK Hospital, Bagalkot comprising 150 patients for a period of 8 months. The study group consisted of the patients admitted with clinical diagnosis of necrotizing fasciitis by different surgeons during this period. Results: Out of 150 patients with necrotizing fasciitis, 121 (80.67%) were male and 29 (19.33%) were females. The maximum number of patients 45 (30%) were found in the age group of 61 to 70 years. 62 patients had Type II Diabetes Mellitus,13 patients were on steroids, 7 patients had liver disease. The culture and sensitivity reports from these 150 patients was positive for growth in 136(90.66 %). The most common Gram positive bacterial isolate was Staphylococcus aureus 48 (45.28 %) and Gram negative bacterial isolate was Pseudomonas aeruginosa 46 (38.33%). The antibiotic administration was a combination of Cefperazone-sulbactum (or), piprecallin-tazobactum (or), aminoglycosides for gram negative coverage and clindamycin (or) trimethoprim-sulphamethoxazole for gram positive coverage. Anaerobic coverage was with metronidazole/tinidazole. The mortality rate was 11.33% and the common isolate in these patients from wound swab was Acetinobacter with sensitivity only to colistin and tigicycline followed by klebsiella. Conclusions: Males with age more than 60 years having diabetes mellitus were more prone to necrotizing fasciitis. Most common Gram positive bacterial isolate was Staphylococcus aureus and Gram negative bacterial isolate was Pseudomonas aeruginosa.